Application of random elements in ISS. Issue 3 (29th January 2020) - Yan, Xuehu; Lu, Yuliang; Liu, Lintao; Li, Xia; Liu, Jingju; Yang, Guozheng
Abstract : The ( k, n ) ‐threshold image secret sharing (ISS) encodes a secret image into n shares. When k or more shares are obtained, the secret image can be decoded; however, less than k shares could decode none of the secret image. ISS primarily includes polynomial‐based ISS and visual secret sharing (VSS). In this study, the authors find that the random elements in ISS can be used not only to hide information but also to obtain more features such as multiple decryptions and comprehensible share. They have established an application model of random elements that is suitable for both polynomial‐based ISS and VSS. On the basis of the model, they have extended three algorithms to achieve information hiding, multiple decryptions and comprehensible share. Experiments indicate the effectiveness of these algorithms.